Investigating the perceptions of taxpayer towards the adoption of individual electronic tax filing system (E-Filing): A case study on UiTM Pahang's accounting lecturers / Nur Syazwani Mohammad Fadzillah and Mohamad Ridhuan Mat Dangi - Mohammad Fadzillah, Nur Syazwani; Mat Dangi, Mohamad Ridhuan (2013)
The adoption of E-Filing system is to provide an application on filling and filing the income tax return form that can be made electronically through the internet (Inland Revenue Board Malaysia). It is initiated in Malaysia in the year 2006 as part of the E-government services mainly to provide a convenient way for taxpayers paying their taxes. The Inland Revenue Board Malaysia (IRBM) is the responsible government institution to manage the tax paying process and it can be done either manually or through the E-Filing system. With the objective to encourage citizens using ICT, the E-Filing system if it is used properly can provide many benefits such as reducing the operating cost of collecting tax, reducing error, saving time and providing a user friendly service. However, the use of E-Filing system in Malaysia has not yet achieved the high remarks. This is supported by the study conducted by Ramoo (2006) which reported that only 120,000 tax returns done through E-Filing represents only 1.2% of the population of taxpayers. While Kwai Fatt and Ming Ling (2008) indicates that there are users who attempt to use E-Filing for the convenience, speed filing and to get faster tax refund whereas there are also users who intend to use E-Filing but failed to do so due to the slow networks thus discourage them to proceed using the system. Therefore this paper attempts to investigate the users' perceptions towards the use of the E-Filing system in terms of the awareness, satisfaction, easiness, risk exposure and usefulness in using the system by focusing on UiTM Pahang's accounting lecturers as the respondents. On average, the result reflects positive perception of taxpayers towards the implementation of e-Filing system for their tax assessment. Further, most of the respondents agree and strongly agree that they are aware of the e-Filing system and also agree to be satisfied with the services provided in e-Filing system. In addition, respondents agree that e-Filing system is easy to use, neither agree nor disagree that e-Filing system is risky and they agree that e-Filing system is useful to taxpayers.